Material jetting additive manufacturing: An experimental study using designed metrological benchmarks - Yap, Yee Ling (2017)
Additive manufacturing (AM) technique allows the creation of parts with a high degree of design complexity by building three-dimensional (3D) parts layer-by-layer. Many of the current restrictions of design for manufacturing (DFM) as well as design for assembly (DFA) are no longer applicable for AM due to the lack of needs for tooling. Instead, it is critical to establish the manufacturing limits and design guidelines to achieve optimal production outcomes. This can be achieved through manipulation of process parameters.